Etarch: projeto e desenvolvimento de uma arquitetura para o modelo de título com foco na agregação de tráfego Multicast - Gonçalves, Maurício Amaral (2014)
The original design of the Internet was started over forty years ago, in a totally different context of today s. At that time, the network gained new purposes and began to be used in areas and activities that would have been unthinkable during its design. New applications based on networks usage brought a new set of requirements, most of whom were not adequately met due to limitations in architecture. Although the original specification of the Internet has an important role in its popularization, today it represents the main limiter of its evolution, which fosters the thought that the architecture should be reviewed in a clean slate approach. This strategy encourages innovation in the proposals for future networks, by not submitting them to the limitations of the current architecture, and free researchers from the problem of supporting legacy networks. In this context, the Entity Title Model represents a revolutionary way to semantically understand the new Internet requirements, also managing the communication entities and their capabilities, in order to define and implement the best strategies for the treatment of communication. The materialization of this model is performed by Entity Title Architecture, a new flexible architecture that proposes a rereading of important aspects of computer networks, particularly in strategies for addressing and routing.This work proposes an implementation of this architecture through a prototype based on the Open Flow specification, and a practical application with the multicast communication requirement. The proposed approach is able to provide the multicast service efficiently, and with an appropriate solution at the network layer, which is naturally supported by the architecture. Are also presented in this paper the results of some comparative experiments with a video application, first implemented using the TCP/IP architecture with unicast and multicast services, and then, using the Entity Title Architecture, focusing on traffic aggregation through multicast. The results showed that the bandwidth tests with the proposed approach remains constant, while in TCP/IP approach with unicast services, it grows linearly, proportional to the number of connected client. On TCP/IP approach with multicast services, the pattern of bandwidth consumption is similar, however, the approach Entity Title Architecture has won by: decreasing the unnecessary overhead in communication, and thus using less bandwidth; providing better strategies for the control plane, by separating the data plane; and improving the multicast addressability, based on the use of a unique designation, unambiguous and independent of topology; and finally, by presenting a proposal for deployment in real network, because of the Openflow broad support by leading equipment suppliers.